Media and journalism professionals a practical career guide - Hamilton, Tracy Brown (Practical career guides, 2021)
"Media and Journalism Professionals: A Practical Career Guide includes interviews with professionals in a field that has proven to be a stable, lucrative, and growing profession"-- Provided by publisher.